The socio-economic implication of climatic change, desert encroachment and communal conflicts in Northern Nigeria (2010)
The economic activities in Nigeria clearly show that over 60 percent of the population are engaged in agriculture for their livelihoods directly or indirectly. However overtime especially in the last decade, a dwindling state of agriculture and the decreasing number of farming population mostly in Northern Nigeria, known for the production of over 70 percent of the food crops in the country and other West African countries call for concern. Recent geographical survey has attributed these happenings to desert encroachment into farmlands caused by the changes in climatic conditions. In view of these, this study therefore seeks to observe the adjustment and coping strategies of individuals in the affected communities, it examines the communal conflicts among the people and government interventions in reducing the problems associated with climatic change. The study employed principally qualitative methodology: in-depth interviews, observations and focus group discussions, among a cross section of 1200 households drawn randomly and via a snowballing sampling method in four states (Sokoto, Zamfara, Kano and Borno), in Northern Nigeria. Major findings from the study showed that desert encroachment on farmlands is forcing a lot of youths to migrate and seek non-agricultural employment in urban centres, as well as deviant survival strategies such as crime and prostitutions. It was also observed, that as desert encroaches farmlands, community disputes and conflicts over fertile lands increased, and the problem of internally displaced persons were inevitable. Lastly, government interventions were claimed by 70 percent of the respondents to be non existent, slow and limited to economic compensations in some communities. This study concludes and recommends among other things, the need for government, the farming population, and the scientific communities to help in averting desert encroachment and the emanating conflict from climate change.